Settings for open innovation arena: three dimensions to consider (conditions, process and resources) - Sivam, Ashwin Kumar Chandrasekar (2018)
The purpose behind this dissertation is to examine the settings for Open Innovation arena. More particularly the dissertation looks at how a firm can make conditions for taking advantage of outside performers' knowledge at the crossing point of the firm boundary and the outside world, in a composed path by making a physical place that encourages collaboration and permits the firm to use remotely accessible information in a compelling way. Such physical spots mean open Innovation arenas and until now no much studies by researcher and scholars have been carried until now. The dissertation incorporates open innovation literature that examines the current standings on factors that are considered to impact a firm’s capacity to embrace and practice open innovation. It contains literature review and results of a survey conducted among 25 researchers from INESC TEC, the host Institution of the author. The main results show that INESC TEC promotes innovations and brings together a wide range of conditions that encourage open innovation. The three dimensions considered in this study are near the 75th percentile, which is a good indicator. The best dimension in INESC TEC seems to be Conditions (77,14%), followed by Resources (71,04%). Processes appears at the end (69,82%). From a more focused perspective, everything indicates that: • the organization must improve in its innovation strategy as a plan of action with quantitative purposes and targets on long and medium term; • the organisation must improve its training policy for its staff towards innovation, should have adequate structures for managing knowledge and should also develop the information and communication systems to enable the innovation process; • the organisation must improve in developing its systematic processes for interdepartmental co-operation.